THE ROLES OF HOUSEWIFES IN INFORMAL SECTOR (Study on Production of Batu Kapur in Desa Mangkung Lombok Tengah) - Rohimi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
This study was examined the role of women as the housewives in Mangkung Village who work as laborers inthe process of producing limestone. It used qualitative methods to collect data like interviews, observation, anddocumentation. The purpose of this research was to find out how were the role of women who works with men inlimestone production work. The results of this study proved that the women strongly participate in the work oflimestone production processes with men, even the work of women in limestone production was more dominantthan the male laborers. And what is the role of women who have become housewives who take part andparticipate in and work together and collaborate with men in the same scope of work, namely in the process ofproducing limestone. And the motivating factors for working as limestone production laborers are (a) weakfamily economy, (b) preserving cultural work, and (c) weak insight and knowledge. While the obstacles faced byhousewives as laborers in the production of limestone. First, physical constraints such as the severity of the workdone in the production of limestone, such as destroying limestone after burning, raising and lowering lime whengoing to marketing, even they use safety devices such as masks and gloves to maintain their safety and physicalhealth when work. Second, the constraints on his position as a housewife who must prioritize their primarywork in the house such as preparing the needs of their husbands and children. Do not arrive at the existence ofwork outside the house as a laborer of lime production and forget about his responsibilities as a wife